Cell-free microRNAs: potential biomarkers in need of standardized reporting - Kirschner, Michaela B.; van Zandwijk, Nico; Reid, Glen (Frontiers in Genetics, 2013)
MicroRNAs are abundantly present and surprisingly stable in multiple biological fluids. These findings have been followed by numerous of reports revealing the clinical potential of using microRNA levels in body fluids as a biomarker of disease. Despite a rapidly increasing body of literature, the field has failed to adopt a set of standardized criteria for reporting the methodology used in the quantification of cell-free microRNAs. Not only do many studies based on RT-qPCR fail to address the MIQE criteria but frequently there is also a distinct lack of detail in descriptions of sample source and RNA isolation. As a direct result, it is often impossible to compare the results of different studies, which in turn, hinders progress in the field. To address this point, we propose a simple set of criteria to be used in conjunction with MIQE to reveal the true potential of cell-free microRNAs as biomarkers.